2022
DOI: 10.3389/fpsyg.2022.863300
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal survey of depressive symptoms among university students during the COVID-19 pandemic in Japan

Abstract: While changes in response to the different stages of the pandemic remain unknown, this study investigated the longitudinal impact of the COVID-19 pandemic on depressive symptoms in Japanese university students and identified factors associated with new onset of depression and suicidal ideation. Two surveys were conducted at one university in Akita, Japan, during the first COVID-19 outbreak period (T1: May–June 2020) and 1 year later (T2: March–May 2021). Moderate depressive symptoms were defined as a Patient H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…An online study from Italy found an increase in new-onset major depressive disorders in the first and second wave among the general population ( 72 ). A longitudinal survey among university students in Japan found that 11.8% had a new-onset of depressive symptoms, supporting our findings ( 73 ).…”
Section: Discussionsupporting
confidence: 90%
“…An online study from Italy found an increase in new-onset major depressive disorders in the first and second wave among the general population ( 72 ). A longitudinal survey among university students in Japan found that 11.8% had a new-onset of depressive symptoms, supporting our findings ( 73 ).…”
Section: Discussionsupporting
confidence: 90%
“…1101 To provide better services, prospective studies would be helpful to design that evaluate risk factors at the start of the study (ideally at university/college enrolment) that help predict those students expected to need help in the short, medium, and long term. Several contributions regarding the role of the COVID-19 pandemic evidenced (Meda et al, 2021;Nomura et al, 2022;Weber et al, 2022) that such studies can be (i) conducted with little or no specific funding and (ii) they can help better understand the mental disorder development trajectory in a population at high risk of distress and maladjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Porter et al [25] reported that the prevalence of mild-to-severe depression as measured using the PHQ-8 was 9.5% among the young population, while Luong et al [26] reported a prevalence rate of 18.4% for moderate-to-severe depression (PHQ-9 scores) among pregnant women in Vietnam. Other studies using the PHQ-9 have reported that the rate of moderate-to-severe depressive symptoms was higher among Vietnamese immigrants than among Japanese citizens: 17.9% among adults aged 18 years and older in 2020; [27] 11.6% in 2020 and 16.6% in 2021 among college students; [28, 29] and 14.8% among hospital workers in 2020. [30] The current evidence indicates that depressive symptoms among Vietnamese immigrants in Japan appear to be more severe than those among Japanese and Vietnamese individuals living in their home countries.…”
Section: Discussionmentioning
confidence: 99%